Atividade da delta aminolevulinato desidratase sangüínea e o estresse oxidativo em pacientes hemodialisados - Valentini, Juliana (2007)
The acid aminolevulinato dehydratase (δ-ALA-D) is a thiol enzyme involved in tetrapirrólicos composite biosynthesis, as heme. This enzyme is inhibited by some metals, having been also its inhibition a pointer of poisoning for lead (Pb). Additionally, many studies suggest its inhibition as a marker of it oxidative stress, due the high affinity of groups - SH of the enzyme to the pró-oxidantes agents. Patients with chronic renal insufficience (IRC) under treatment of hemodialysis have oxidative stress amplified, as well as increased aluminum levels. The objectives of this study had been to evaluate in patients IRC under treatment of hemodialysis (HD) and healthly individuals, the effect of the levels of reactive species to the acid tiobarbitúrico (TBARS) in the plasma, a marker of comumente estresse it oxidativo used, and aluminum levels (Al) on the activity of blood δ-ALA-D. Also the envolvement of groups - SH in the activity of the enzyme was evaluated, through the incubation in vitro with dithiothreitol (DTT), a reducing agent. The joined results had been, activity of diminished δ-ALA-D, the increased of TBARS levels and Al (p<0.05) in hemodialisados patients compared with the group of healthly individuals. The activity of the enzyme after incubation with DTT significantly was increased in the hemodialisados ones, but it did not reach the levels found in the healthly individuals. Moreover, the activity of the enzyme was correlated negative with the TBARS levels and Al, however, the partial correlation only showed influence of the TBARS in the activity of the enzyme. It is concluded that in HD patients the activity of δ-ALA-Dsignificantly is diminished, that its groups - SH are inhibited, provalmente had to oxidative stress. However the inhibition of the groups - SH is not the only cause of reduction of the enzymatic activity, since the DTT did not revert its activity the normal levels.